Makna Komunikasi Emosional Dalam Film Pendek Animasi “Pupus – Cangkir Profesor” Melalui Simbol Cangkir Dan Relasi Antargenerasi - Rizky Saputri; Fitria Yuliani (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to explore the meaning of emotional communication in the animated short film Pupus – Cangkir Profesor through the analysis of symbolic elements and intergenerational relationships. The research focuses on how visual symbols, particularly the cup, function as a medium to convey emotional bonds, memories, and values between characters of different generations. The method used is a qualitative approach with semiotic analysis, applying Roland Barthes’ framework to interpret the denotative, connotative, and mythical levels of meaning in selected scenes from the animation. Data were obtained by observing and documenting key visual moments, then analyzed to uncover the layered meanings embedded in the narrative and visual cues. The findings reveal that the cup symbol carries significant sentimental value, representing love, remembrance, and emotional continuity between the younger and older characters. It also reflects cultural values of respect, care, and the transmission of wisdom across generations. The study concludes that visual symbols in animated storytelling can serve as powerful tools to evoke empathy, strengthen emotional engagement, and preserve intergenerational connections, making them effective in both artistic and communicative contexts.